The Increase of Teacher's Commitment to The Organisation Through Servant Leadership Reinforcement of The Principal and Job Satisfaction - Sutji Harijanto; B. Dwi Yuniar Rahmawaty; Muhammad Entang (JETL (Journal of Education, Teaching and Learning), 2021)
The purpose of this study is to empirically determine the improvement of teacher's commitment to the organisation by observing its connection with servant leadership of the principal and job satisfaction, with respondents being Permanent Teachers of the Foundation (GTY) of Private Junior High School in Cibinong District, Bogor Regency. The number of research samples of 183 teachers was taken randomly using the proportional random sampling technique. The method used was the correlation method. Hypothesis testing was carried out using parametric statistical analysis in simple and multiple linear regression analysis, simple and multiple correlation analysis, and partial analysis with a significance level of = 0.01 and = 0.05. This study resulted in four conclusions. First, there is a significant positive correlation between servant leadership (X1) and teacher's commitment to the organisation (Y), which is indicated by a simple linear regression equation Ŷ = 63.094 + 0,501X1. with correlation coefficient ry1 = 0.73, coefficient of determination Ry12 = 0.5361. Second, there is a very significant positive correlation between job satisfaction (X2) and teacher’s commitment to the organization (Y) which is indicated by the linear regression equation Ŷ = 56.35 + 0.552X2 with correlation coefficient ry2 = 0.66, coefficient of determination Ry22 = 0,4343. Third, there is a significant positive correlation between servant leadership and job satisfaction collectively with the teacher's commitment to the organisation, which is indicated by the equation Ŷ = 35.50 + 0.372X1 + 0.34X2 with a correlation coefficient ry.12 = 0.81 and coefficient of determination Ry.122= 0.665. Fourth, commitment to the organisation of GTY's Private Junior High School in Cibinong District, Bogor Regency can be enhanced through strengthening servant leadership and job satisfaction.